2021
DOI: 10.3390/dj9120147
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Therapies for the Management of Dental Caries—A Literature Review

Abstract: In recent years, due to a better understanding of the caries pathology and advances in dental materials, the utilization of non-invasive and minimally invasive techniques that delay/obviate the need for traditional restorations has started gaining momentum. This literature review focuses on some of these approaches, including fluoride varnish, silver diamine fluoride, resin sealants, resin infiltration, chemomechanical caries removal and atraumatic restorative treatment, in the context of their chemistries, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 182 publications
(273 reference statements)
0
18
0
14
Order By: Relevance
“…It is known that demineralized but non-cavitated enamel lesions can be remineralized [29]. Recent studies suggested that demineralized but structurally intact dentin can be remineralized as well [3]. Nonetheless, the traditional use of the probe has been recommended also in a recent monograph [30].…”
Section: Dental Cariesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that demineralized but non-cavitated enamel lesions can be remineralized [29]. Recent studies suggested that demineralized but structurally intact dentin can be remineralized as well [3]. Nonetheless, the traditional use of the probe has been recommended also in a recent monograph [30].…”
Section: Dental Cariesmentioning
confidence: 99%
“…In this connection, minimally invasive dentistry (MID) is discussed. The concept of MID applied for the caries treatment includes modified methods of tooth preparation based, as far as possible, on individual evaluation of the caries progression rate [1][2][3][4][5]. This concept is applicable also to periodontal conditions [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride has a long-term relationship with dental practice and preventive dentistry; documents older than 200 years refer to the probable link between fluoride and carious activity [5]. Future research seems to aim for improving the antimicrobial and anti-degradative properties of current restoration materials [6], associated with the modification of their composition in order to reduce microbial attachment and biofilm formation [7].…”
Section: Introductionmentioning
confidence: 99%
“…As técnicas restauradoras convencionais utilizadas no tratamento da cárie envolvem a remoção de grandes quantidades da estrutura dentária para eliminar tecidos contaminados por bactérias cariogênicas, resistir às forças oclusais e remover a dentina desmineralizada (Li et al, 2018;Schwendick et al, 2021). No entanto, podem resultar em exposição pulpar, enfraquecimento da estrutura dentária e perda de vitalidade, o que implica na necessidade de tratamentos restauradores ainda mais complexos, que conduzem o dente à um ciclo restaurador repetitivo, referido como o "espiral da morte da restauração" (Barros et al, 2020;Desai;Li et al, 2018). Contudo, a chegada de materiais dentários adesivos e bioativos tornaram desnecessária a remoção extensa da estrutura dentária para retenção da restauração (Desai;.…”
Section: Introductionunclassified